Zinc-containing catalyst as well as preparation method and application thereof

By using specific molar ratios of amino compounds, aldehyde compounds and zinc salts in the polymerization reaction, zinc-containing catalysts with high specific surface area and nanopores are prepared, which solves the problems of low catalytic activity of existing catalysts and difficult to control by-products. The synthesis of aliphatic polycarbonate is achieved efficiently.

CN119409960AActive Publication Date: 2025-02-11CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411449340.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-17
Publication Date
2025-02-11
Estimated Expiration
2044-10-17

AI Technical Summary

Technical Problem

The existing catalysts have low catalytic activity and long reaction time when preparing aliphatic polycarbonate, require high polymerization pressure and organic solvents, and the by-product cyclic small-molecule carbonate is difficult to control and the catalytic efficiency is low.

Method used

By polymerizing amino compounds, aldehyde compounds and zinc salts under specific molar ratios and conditions, a zinc-containing catalyst with large specific surface area and nano-level pores are prepared for catalyzing epoxycyclohexane and ethylene oxide. Copolymerization reaction with carbon dioxide.

Benefits of technology

It improves catalytic efficiency, shortens reaction time, reduces polymerization pressure, reduces the generation of by-products, simplifies the separation of products and catalysts, and significantly improves catalytic performance and stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_4
    Figure SMS_4
  • Figure FDA0005088616410000011
    Figure FDA0005088616410000011
Patent Text Reader

Abstract

The invention provides a zinc-containing catalyst as well as a preparation method and application thereof, and belongs to the technical field of catalysts. According to the present invention, the amino compound, the aldehyde group compound and the zinc salt are subjected to the polymerization reaction under the catalysis of the catalyst to prepare the zinc-containing catalyst, and the obtained zinc-containing catalyst has characteristics of large specific surface area, nano-scale pore channels, high catalysis efficiency when used for the catalytic synthesis of polycarbonate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to the technical field of catalysts, and in particular to a zinc-containing catalyst and a preparation method and application thereof. Background Art

[0002] With the rapid development of modern industry, humans emit a large amount of carbon dioxide gas into the atmosphere every year, causing the carbon dioxide content in the atmosphere to increase year by year. A large amount of carbon dioxide gas has led to a serious greenhouse effect. Controlling and reducing carbon dioxide emissions has become a consensus among countries around the world. Carbon dioxide is also an important carbon resource in nature. The development and comprehensive utilization of carbon dioxide has always been an important research direction in C1 chemistry. At present, the world's carbon dioxide is mainly used in carbonated beverages, fire extinguishing agents, refrigerants, supercritical extraction solvents and other fields. The demand is small, the market potential is not large, and the application range is limited. It cannot be used for large-scale industrial applications.

[0003] With the increasing shortage of global carbon resources, especially petroleum resources, and the high attention to the greenhouse effect caused by carbon dioxide, countries around the world have increased their efforts in the research and comprehensive utilization of carbon dioxide in the chemical industry. One of the most promising utilization methods is to copolymerize carbon dioxide with epoxy compounds to prepare aliphatic polycarbonates. The most commonly used epoxy monomers are propylene oxide and cyclohexane oxide, and the copolymerization products are polypropylene carbonate and polycyclohexene carbonate, respectively. However, carbon dioxide is chemically inert and difficult to participate in copolymerization reactions. Therefore, how to prepare aliphatic polycarbonates with excellent performance under relatively mild conditions is a difficulty in this research, and the main solution is to develop and apply catalysts with high catalytic efficiency and good selectivity.

[0004] At present, researchers have developed catalytic systems such as diethyl zinc catalytic system, zinc carboxylate catalytic system, rare earth catalytic system, Schiff base metal complex, double metal cyanide (DMC) catalytic system, etc. Most of the above-mentioned catalysts used to prepare polycarbonate have low catalytic activity, require a long reaction time and high polymerization pressure, require organic solvents, and are accompanied by the production of cyclic small molecular carbonate by-products, low catalytic efficiency, and difficulty in separating products and catalysts. Summary of the invention

[0005] The purpose of the present disclosure is to overcome the deficiencies of the prior art and to provide a zinc-containing catalyst and a preparation method and application thereof. The zinc-containing catalyst has a large specific surface area and nano-scale pores and is used for catalytic synthesis of polycarbonate with high catalytic efficiency.

[0006] To achieve the above object, the technical solution adopted by the present disclosure is: to provide a method for preparing a zinc-containing catalyst, comprising the following steps:

[0007] An amino compound, an aldehyde compound, a zinc salt, a catalyst and a solvent are mixed to carry out a polymerization reaction to obtain a zinc-containing catalyst;

[0008] The structural formula of the amino compound is shown in Formula 1, and the structural formula of the aldehyde compound is shown in Formula 2:

[0009]

[0010] The zinc salt is at least one of zinc chloride, zinc acetate, diethyl zinc, zinc glutarate, zinc cobalt cyanate, and N,N'-disalicylicaldehyde ethylenediamine zinc;

[0011] The catalysts are acetic acid and p-toluenesulfonic acid.

[0012] In one embodiment, the molar ratio of the amino compound, the aldehyde compound and the zinc salt is amino compound:aldehyde compound:zinc salt=(1:1:1)-(1:4:4).

[0013] In one embodiment, the polymerization reaction temperature is 60-150° C.; and / or the polymerization reaction time is 10-48 hours.

[0014] In one embodiment, the molar ratio of acetic acid to p-toluenesulfonic acid is (1:1)-(1:2).

[0015] In one embodiment, the amount of the solvent tetrahydrofuran used is 40-120 mL.

[0016] In one embodiment, the ratio of the mass of the catalyst to the total mole of the amino compound and the aldehyde compound is 0.1 g: (1-2 mmol).

[0017] In one embodiment, after the polymerization reaction is completed, the obtained product is filtered, washed, Soxhlet extracted and dried in sequence to obtain a zinc-containing catalyst.

[0018] In one embodiment, the solvent is at least one of chloroform, ether, benzene, methyl acetate, tetrahydrofuran, acetone, methanol, petroleum, chlorophenol, ethylene dichloride, and carbon tetrachloride.

[0019] On the other hand, a zinc-containing catalyst is provided, wherein the zinc-containing catalyst is prepared by the preparation method of the zinc-containing catalyst.

[0020] In another aspect, the invention provides use of the zinc-containing catalyst in catalytic synthesis of polycarbonate.

[0021] In one embodiment, the use comprises the following step: copolymerizing cyclohexene oxide, ethylene oxide and carbon dioxide in the presence of a zinc-containing catalyst.

[0022] In one embodiment, the amount of the zinc-containing catalyst is 10-20 mg / mL; and / or the molar ratio of cyclohexene oxide to ethylene oxide is 5:1 to 1:5; and / or the pressure of carbon dioxide is 1 to 5 MPa; and / or the copolymerization reaction temperature is 60 to 120° C.; and / or the copolymerization reaction time is 5 to 12 hours.

[0023] Compared with the prior art, the beneficial effects of the present invention are as follows: the present invention uses a catalyst to catalyze the polymerization reaction of an amino compound, an aldehyde compound and a zinc salt to prepare a zinc-containing catalyst. The obtained zinc-containing catalyst has a large specific surface area and nano-scale pores, and is used for catalytic synthesis of polycarbonate with high catalytic efficiency. DETAILED DESCRIPTION

[0024] With reference to the detailed description of the following embodiments, it will be easier to understand the advantages and features of the present disclosure and the methods for achieving the advantages and features. However, the present disclosure can be implemented in various other forms and should not be construed as being limited to the embodiments set forth herein. The embodiments disclosed herein are provided so that the disclosure of the present disclosure will be thorough and complete, and the scope of the present disclosure will be fully conveyed to those skilled in the art.

[0025] The terms used in the specification are intended to describe certain embodiments only and should by no means limit the present disclosure.Expressions in the singular include the meaning of the plural form unless clearly used otherwise.

[0026] Unless otherwise defined, all terms (including technical and scientific terms) used in this disclosure have the same meaning as those commonly understood by ordinary technicians in the field to which this disclosure belongs. Any term defined in a comprehensive dictionary should be interpreted as having the same meaning in the context of the relevant field.

[0027] Hereinafter, the zinc-containing catalyst and the preparation method and application thereof according to the present disclosure will be described in detail.

[0028] The present disclosure provides a method for preparing a zinc-containing catalyst, comprising the following steps:

[0029] An amino compound, an aldehyde compound, a zinc salt, a catalyst and a solvent are mixed to carry out a polymerization reaction to obtain a zinc-containing catalyst;

[0030] The structural formula of the amino compound is shown in Formula 1, and the structural formula of the aldehyde compound is shown in Formula 2:

[0031] CAS: 106-50-3;

[0032] CAS: 2243590-42-1, purchased from Alpha Chemical Co., Ltd.;

[0033] The zinc salt is at least one of zinc chloride, zinc acetate, diethyl zinc, zinc glutarate, zinc cobalt cyanate, and N,N'-disalicylicaldehyde ethylenediamine zinc;

[0034] The catalysts are acetic acid and p-toluenesulfonic acid.

[0035] In the present disclosure, acetic acid and p-toluenesulfonic acid are used as catalysts to catalyze the polymerization reaction of amino compounds, aldehyde compounds and zinc salts to obtain a zinc-containing catalyst with a large specific surface area and nanopores. The zinc-containing catalyst uses a benzene ring as a structural unit, and the amino compound, aldehyde compound and zinc salt are interconnected by covalent bonds, so that the zinc-containing catalyst has a rigid structure, which can effectively support the nanopore structure of the zinc-containing catalyst and increase the specific surface area of ​​the zinc-containing catalyst. Thus, the exposed number of catalytic sites of the zinc-containing catalyst and the utilization efficiency of the catalytic sites are increased, and the pore collapse of the zinc-containing catalyst during use is avoided, thereby improving the catalytic performance of the zinc-containing catalyst.

[0036] Specifically, zinc serves as the active center of the zinc-containing catalyst. In order to obtain a zinc-containing catalyst with high catalytic performance, it is necessary to control the content of zinc salt during the preparation process of the zinc-containing catalyst. If the content of zinc salt is too high, the specific surface area of ​​the zinc-containing catalyst decreases, resulting in a sudden decrease in the catalytic performance of the zinc-containing catalyst. If the content of zinc salt is too low, the thermal stability and chemical stability of the zinc-containing catalyst are low. Therefore, the present invention selects the molar ratio of amino compound, aldehyde compound and zinc salt as amino compound: aldehyde compound: zinc salt = (1:1:1)-(1:4:4); the number of functional groups and nanopores of the zinc-containing catalyst can be effectively increased; the catalytic performance and stability of the zinc-containing catalyst can be improved; preferably, the molar ratio of the amino compound, aldehyde compound and zinc salt is amino compound: aldehyde compound: zinc salt = (1:1:1)-(1:3:3); more preferably, the molar ratio of the amino compound, aldehyde compound and zinc salt is amino compound: aldehyde compound: zinc salt = (1:1:1)-(1:2:2). The zinc-containing catalyst prepared with a molar ratio within the above range can effectively ensure that the catalytic performance and stability are maintained within a suitable range. At the same time, a suitable reaction temperature and time are further selected to improve the catalytic performance and stability of the product.

[0037] Specifically, the polymerization reaction temperature is 60-150° C.; and / or the polymerization reaction time is 10-48 hours.

[0038] In the present disclosure, the polymerization reaction temperature may be 60°C, 70°C, 80, 90°C, 100°C, 110°C, 120°C, 130°C; or a range consisting of any two of the above values; preferably 110-125°C, more preferably 120°C.

[0039] The polymerization reaction time can be 10 h, 15 h, 20 h, 25 h, 30 h, 35 h, 40 h, 44 h, 48 h; it can also be a range consisting of any two of the above values; preferably it is 30-45 h, more preferably 40 h.

[0040] The temperature and time of the polymerization reaction will affect the catalytic performance and stability of the zinc-containing catalyst. If the temperature of the polymerization reaction is too high or the time of the polymerization reaction is too long, the system of the polymerization reaction will be in a boiling state, thereby reducing the catalytic effects of acetic acid and p-toluenesulfonic acid, and the zinc salt will lose activity, thereby causing the thermal stability and catalytic performance of the zinc-containing catalyst to decrease; if the temperature of the polymerization reaction is too low or the reaction time is too short, the polymerization degree of the zinc-containing catalyst will decrease, causing the mechanical strength and specific surface area of ​​the zinc-containing catalyst to decrease, thereby reducing the catalytic performance and chemical stability of the zinc-containing catalyst. Those skilled in the art can adjust the temperature and time of the polymerization reaction within the range of 60 to 150° C. and 10 to 48 h for the polymerization reaction to obtain a zinc-containing catalyst with better catalytic performance and stability.

[0041] Specifically, the molar ratio of acetic acid to p-toluenesulfonic acid is (1:1)-(1:2).

[0042] If the molar ratio of acetic acid to p-toluenesulfonic acid is too small or too large, the catalytic effect of acetic acid and p-toluenesulfonic acid will be reduced, thereby affecting the polymerization reaction of amino compounds, aldehyde compounds and zinc salts; and further resulting in reduced performance of the zinc-containing catalyst.

[0043] Specifically, the ratio of the mass of the catalyst to the total mole of the amino compound and the aldehyde compound is 0.1 g: (1-2 mmol).

[0044] Specifically, in the present disclosure, in order to further improve the purity of the zinc-containing catalyst, after the polymerization reaction is completed, the obtained product needs to be filtered, washed, Soxhlet extracted and dried in sequence.

[0045] The present disclosure has no particular limitation on the specific operation method of the filtration, and a filtration method well known to those skilled in the art may be used.

[0046] The present disclosure has no particular limitation on the washing solution, and washing can be performed using a washing solution well known in the art, such as deionized water, ethanol, and tetrahydrofuran.

[0047] The present disclosure has no special limitation on the solvent for Soxhlet extraction, and the Soxhlet extraction is performed using a solvent known in the art. The present disclosure prefers dichloromethane, tetrahydrofuran and petroleum ether for Soxhlet extraction, and the specific steps are: the product obtained by washing is subjected to Soxhlet extraction with dichloromethane, tetrahydrofuran and petroleum ether in sequence.

[0048] The present disclosure has no particular limitation on the time of Soxhlet extraction, and those skilled in the art can select a suitable time according to actual needs. The present disclosure selects a Soxhlet extraction time of 48-72 h / time, preferably 60-70 h / time, and more preferably 70 h / time.

[0049] The present disclosure does not specifically limit the specific operation mode of the drying, and a filtering method well known to those skilled in the art can be used. The preferred drying method of the present disclosure is vacuum drying.

[0050] The present disclosure does not specifically limit the drying temperature and time, and those skilled in the art can select appropriate temperature and time according to actual needs. The present disclosure selects a drying temperature of 50-100°C and a drying time of 18-24h; preferably, the drying temperature is 75-95°C and the drying time is 21-23h; more preferably, the drying temperature is 80°C and the drying time is 22h.

[0051] Specifically, in the present disclosure, the solvent is at least one of chloroform, ether, benzene, methyl acetate, tetrahydrofuran, acetone, methanol, petroleum, chlorophenol, ethylene dichloride, and carbon tetrachloride; preferably, the solvent is tetrahydrofuran.

[0052] The present disclosure also discloses a zinc-containing catalyst, which is prepared by the preparation method of the zinc-containing catalyst.

[0053] The present disclosure also discloses the use of the zinc-containing catalyst in catalytic synthesis of polycarbonate.

[0054] Specifically, the application comprises the following steps: in the presence of a zinc-containing catalyst, copolymerizing cyclohexene oxide, ethylene oxide and carbon dioxide.

[0055] Specifically, the dosage of the zinc-containing catalyst is 10-20 mg / mL; and / or the molar ratio of cyclohexene oxide to ethylene oxide is 5:1 to 1:5; and / or the pressure of carbon dioxide is 1 to 5 MPa; and / or the copolymerization reaction temperature is 60 to 120° C.; and / or the copolymerization reaction time is 5 to 12 hours.

[0056] The CAS number of cyclohexene oxide is: 286-20-4.

[0057] The present disclosure can be further demonstrated by way of the following examples, which should not be considered limiting. Unless otherwise stated, the raw materials used in any examples and comparative examples herein are commercially available.

[0058] Example 1

[0059] The preparation method of the zinc-containing catalyst of this embodiment comprises the following steps:

[0060] 0.6 g of acetic acid and 1.72 g of p-toluenesulfonic acid were added to a round-bottom flask; the flask was evacuated, filled with nitrogen and then injected with 50 mL of tetrahydrofuran, and then the aldehyde compound, the amino compound and zinc chloride were added to the round-bottom flask, wherein the molar ratio of the amino compound, the aldehyde compound and the zinc chloride was amino compound: aldehyde compound: zinc chloride = 1:1:1, and heated to 120°C for 48 hours; after the reaction was completed, it was cooled to room temperature and then filtered, and the crude product obtained by filtration was washed with deionized water, and the product obtained by washing was Soxhlet extracted with dichloromethane, tetrahydrofuran and petroleum ether in turn; the product obtained by Soxhlet extraction was heated to 100°C under a vacuum environment and dried for 20 hours to obtain a zinc-containing catalyst.

[0061] Example 2

[0062] The preparation method of the zinc-containing catalyst in this embodiment is different from that in Embodiment 1 only in that zinc acetate is used instead of zinc chloride.

[0063] Example 3

[0064] The preparation method of the zinc-containing catalyst in this embodiment is different from that in Embodiment 1 only in that diethyl zinc is used to replace zinc chloride.

[0065] Example 4

[0066] The preparation method of the zinc-containing catalyst in this embodiment is different from that in Embodiment 1 only in that zinc glutarate is used instead of zinc chloride.

[0067] Example 5

[0068] The preparation method of the zinc-containing catalyst in this embodiment is different from that in Embodiment 1 only in that zinc chloride is replaced by N,N'-disalicylicylaldehyde ethylenediamine zinc.

[0069] Example 6

[0070] The preparation method of the zinc-containing catalyst in this embodiment is different from that in Embodiment 1 only in that the molar ratio of the amino compound, the aldehyde compound and the zinc chloride is amino compound:aldehyde compound:zinc chloride=1:1:2.

[0071] Example 7

[0072] The preparation method of the zinc-containing catalyst in this embodiment is different from that in Embodiment 1 only in that the molar ratio of the amino compound, the aldehyde compound and the zinc chloride is amino compound:aldehyde compound:zinc chloride=1:2:2.

[0073] Example 8

[0074] The preparation method of the zinc-containing catalyst in this embodiment is different from that in Embodiment 1 only in that the molar ratio of the amino compound, the aldehyde compound and the zinc chloride is amino compound:aldehyde compound:zinc chloride=1:2:3.

[0075] Example 9

[0076] The preparation method of the zinc-containing catalyst in this embodiment is different from that in Embodiment 1 only in that the molar ratio of the amino compound, the aldehyde compound and the zinc chloride is amino compound:aldehyde compound:zinc chloride=1:3:3.

[0077] Example 10

[0078] The preparation method of the zinc-containing catalyst in this embodiment is different from that in Embodiment 1 only in that the molar ratio of the amino compound, the aldehyde compound and the zinc chloride is amino compound:aldehyde compound:zinc chloride=1:3:4.

[0079] Embodiment 11

[0080] The preparation method of the zinc-containing catalyst in this embodiment is different from that in Embodiment 1 only in that the molar ratio of the amino compound, the aldehyde compound and the zinc chloride is amino compound:aldehyde compound:zinc chloride=1:4:3.

[0081] Example 12

[0082] The preparation method of the zinc-containing catalyst in this embodiment is different from that in Embodiment 1 only in that the molar ratio of the amino compound, the aldehyde compound and the zinc chloride is amino compound:aldehyde compound:zinc chloride=1:4:4.

[0083] Example 13

[0084] The only difference between the preparation method of the zinc-containing catalyst in this embodiment and that in Embodiment 1 is that the polymerization reaction temperature is 60°C.

[0085] Embodiment 14

[0086] The only difference between the preparation method of the zinc-containing catalyst in this embodiment and that in Embodiment 1 is that the polymerization reaction temperature is 70°C.

[0087] Embodiment 15

[0088] The only difference between the preparation method of the zinc-containing catalyst in this embodiment and that in Embodiment 1 is that the polymerization reaction temperature is 80°C.

[0089] Example 16

[0090] The only difference between the preparation method of the zinc-containing catalyst in this embodiment and that in Embodiment 1 is that the polymerization reaction temperature is 90°C.

[0091] Embodiment 17

[0092] The only difference between the preparation method of the zinc-containing catalyst in this embodiment and that in Embodiment 1 is that the polymerization reaction temperature is 100°C.

[0093] Embodiment 18

[0094] The only difference between the preparation method of the zinc-containing catalyst in this embodiment and that in Embodiment 1 is that the polymerization reaction temperature is 130°C.

[0095] Embodiment 19

[0096] The catalytic performance, thermal stability and chemical stability of the zinc-containing catalysts obtained in each embodiment and comparative example were tested. The testing method is as follows:

[0097] Specific surface area: Nova 600BET surface area and pore size analyzer.

[0098] Catalytic performance: In the presence of a zinc-containing catalyst, cyclohexene oxide, ethylene oxide and carbon dioxide are copolymerized; the parameters of the copolymerization reaction are shown in Table 1.

[0099] Thermal stability: DZ-TGA105 high temperature thermogravimetric analyzer was used to test the thermal stability of the catalyst. Tensile strength: YP-LL-05 double column touch-type tensile and compressive testing machine. The test results are shown in Table 1.

[0100] Table 1

[0101]

[0102] As can be seen from Table 1, the catalytic performance, thermal stability and tensile strength of the zinc-containing catalyst of the present disclosure.

[0103] Comparative Examples 1-5 show that when the zinc salt is zinc chloride, the catalytic efficiency of the obtained zinc-containing catalyst is higher.

[0104] By comparing Example 1 and Examples 6-12, it can be seen that when the molar ratio of the amino compound, the aldehyde compound and the zinc salt is amino compound: aldehyde compound: zinc salt = (1:2:2)-(1:4:4), the catalytic performance and stability of the obtained zinc-containing catalyst are better; when the molar ratio of the amino compound, the aldehyde compound and the zinc salt is amino compound: aldehyde compound: zinc salt = (1:3:3)-(1:4:4), the catalytic performance and stability of the obtained zinc-containing catalyst are excellent.

[0105] By comparing Example 1 and Examples 13-18, it can be seen that when the polymerization reaction temperature is 110-130°C, it is beneficial to improve the catalytic performance and stability of the zinc-containing catalyst; when the polymerization reaction temperature is 120°C, the catalytic performance and stability of the zinc-containing catalyst are optimal.

[0106] Finally, it should be noted that the above embodiments are used to illustrate the technical solution of the present disclosure rather than to limit the protection scope of the present disclosure. Although the present disclosure has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present disclosure can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present disclosure.

Claims

1. A method for preparing a zinc-containing catalyst, characterized in that: The method comprises the following steps: mixing an amino compound, an aldehyde compound, a zinc salt, a catalyst and a solvent, and performing a polymerization reaction to obtain a zinc-containing catalyst; The structural formula of the amino compound is shown in Formula 1, and the structural formula of the aldehyde compound is shown in Formula 2: The zinc salt is at least one of zinc chloride, zinc acetate, diethyl zinc, zinc glutarate, zinc cobalt cyanate, and N,N'-disalicylicaldehyde ethylenediamine zinc; The catalysts are acetic acid and p-toluenesulfonic acid.

2. The preparation method according to claim 1, characterized in that The molar ratio of the amino compound, the aldehyde compound and the zinc salt is amino compound:aldehyde compound:zinc salt=(1:1:1)-(1:4:4).

3. The preparation method according to claim 1, characterized in that: The polymerization reaction temperature is 60-150° C.; and / or the polymerization reaction time is 10-48 hours.

4. The preparation method according to claim 1, characterized in that: The molar ratio of the acetic acid to p-toluenesulfonic acid is (1:1)-(1:2); And / or, the ratio of the mass of the catalyst to the total mole of the amino compound and the aldehyde compound is 0.1 g: (2-5 mmol).

5. The preparation method according to claim 1, characterized in that: After the polymerization reaction is completed, the obtained product is filtered, washed, Soxhlet extracted and dried in sequence to obtain a zinc-containing catalyst.

6. The preparation method according to claim 1, characterized in that: The solvent is at least one of chloroform, ether, benzene, methyl acetate, tetrahydrofuran, acetone, methanol, petroleum, chlorophenol, ethylene dichloride and carbon tetrachloride.

7. A zinc-containing catalyst, characterized in that The zinc-containing catalyst is prepared by the preparation method of the zinc-containing catalyst according to any one of claims 1 to 6.

8. Use of the zinc-containing catalyst as claimed in claim 7 in catalytic synthesis of polycarbonate.

9. The use according to claim 8, characterized in that The application comprises the following steps: in the presence of a zinc-containing catalyst, copolymerizing cyclohexene oxide, ethylene oxide and carbon dioxide.

10. The use according to claim 9, characterized in that The dosage of the zinc-containing catalyst is 10-20 mg / mL; and / or the molar ratio of cyclohexene oxide to ethylene oxide is 5:1 to 1:5; and / or the pressure of carbon dioxide is 1 to 5 MPa; and / or the copolymerization reaction temperature is 60 to 120° C.; and / or the copolymerization reaction time is 5 to 12 hours.

Citation Information

Patent Citations

  • Zinc-based catalyst used for preparing poly(cyclohexene carbonate)

    CN107778195A

  • Method for preparing formamide compound by using MCOF to catalyze CO2 as carbon source at normal temperature and pressure

    CN112920071A

  • Thiophene-based imine-linked covalent organic framework for iodine adsorption

    CN118667105A

  • Novel zinc-containing metal organic framework compound, and method for preparing five-membered cyclic carbonate compound using same as catalyst

    WO2018074675A1